Representative hiring in the interactive theater performance techniques (Al-Academy, 2017)
That researchers in the play Science Find a theatrical form of an experimental creative, and these experiences taken from the innovation space aesthetic dialogue with the receiver, especially since with previous theatrical experience and is an extension of her, because the interactive theater theatrical terms that assume a pattern do from the depth of the relationship between supply playwright and the audience, which alters the receiving skills actually change, and to monitor these differing divided into three classes that include research, methodological framework (Chapter I) and includes, research problem, the importance of research and the need to him, the goal of the research, the limits Find it border, and the theoretical framework (Chapter II) and includes the first topic: the interactive theater and understandable and supporting infrastructure. And techniques, and the second section approaches the analog performance in the interactive theater traditional Chapter III, theater and includes procedures for research and presentations selected, Chapter IV of research and discussion, conclusions, recommendations and proposals results and concludes research with the most important references and sources and summary in English and reach the researcher to the group of the outcome of the most important * The interactive theater gives the recipient an opportunity ask questions inside the display to express their view and Hah as well as strengthening the revolutionary dimension of theater. * Interactive Theatre Lovers aesthetically pleasing form a new equation in the question and the answer is negative, towards clarifying question now theater and this cannot be achieved in the Aristotelian theater and his opponents